Comparing the Functional Performance of Children and Youths With Autism, Developmental Disabilities, and No Disability Using the Revised Pediatric Evaluation of Disability Inventory Item Banks. - Ying-Chia Kao; Kramer, Jessica M.; Liljenquist, Kendra; Feng Tian; Coster, Wendy J. (American Journal of Occupational Therapy)
OBJECTIVE. We compared the functional performance of children with autism spectrum disorders (ASD), intellectual and developmental disabilities (IDD), and without disabilities using the revised Pediatric Evaluation of Disability Inventory--Computer Adaptive Test (PEDI--CAT) Social/Cognitive, Daily Activities, and Responsibility domains. METHOD. A nationally representative sample of parents of children ages 0-21 without disabilities (n = 2,205), with ASD (n = 108), or with IDD (n = 150) completed an online survey. We obtained predicted PEDI--CAT scaled scores for three reference ages (5, 10, 15) from a modified analysis of covariance model and compared each group's scores using contrasts of the regression parameters. RESULTS. We found no significant differences between the ASD and IDD groups. The group with ASD demonstrated significantly lower performance than the group without disabilities across the three domains at ages 10 and 15. CONCLUSION. Scores on the PEDI--CAT differentiated the group with ASD from the group without disabilities. Children with ASD and IDD did not demonstrate different performance profiles.